L‐arginine as a potential GLP‐1‐mediated immunomodulator of Th17‐related cytokines in people with obesity and asthma - Shu‐Yi Liao; Angela Linderholm; Megan R. Showalter; Ching‐Hsien Chen; Oliver Fiehn; Nicholas J. Kenyon (Wiley, 2021)
Abstract Obesity is considered as a risk factor for COVID‐19 with insulin resistance and increased production of inflammatory cytokines as likely mechanisms. Glucagon‐like peptide‐1 (GLP‐1) agonists and inhaled nitric oxide are proposed therapeutic approaches to treat COVID‐19 because of their broad anti‐inflammatory effects. One approach that might augment GLP‐1 levels would be dietary supplementation with L‐arginine. Beyond cytokines, multiple studies have started to investigate the relationship between new‐onset diabetes and COVID‐19. In a posthoc analysis of a randomized, placebo‐controlled human clinical trial of L‐arginine supplementation in people with asthma and predominantly with obesity, the results showed that 12 weeks of continuous L‐arginine supplementation significantly decreased the level of IL‐21 (p = 0.02) and increased the level of insulin (p = 0.02). A high arginine level and arginine/ADMA ratio were significantly associated with lower CCL‐20 and TNF‐α levels. The study also showed that L‐arginine supplementation reduces cytokine levels and improves insulin deficiency or resistance, both are two big risk factors for COVID‐19 severity and mortality. Given its safety profile and ease of accessibility, L‐arginine is an attractive potential therapeutic option that allows for a cost‐effective way to improve outcomes in patients. An expedition of further investigation or clinical trials to test these hypotheses is needed.